Effect of Citric Acid Cross-Linking on the Functional and Mechanical Properties of Chitosan-Based Edible Films with Aloe vera Gel and Red Ginger Extract - Cahayo, Mafud; Iftitah, Elvina Dhiaul; Mardiana, Diah (Indonesian Journal of Chemistry, 2026)
Chitosan-based edible films (CBEFs) suffer from poor water vapor barrier and mechanical properties. This study investigated the effect of citric acid cross-linking and bioactive additives, including Aloe vera gel (AVG) and red ginger extract (RGE), on the physicochemical, functional, structural, and thermal properties of CBEFs. Eight formulations were prepared by dissolving 1% chitosan in either 1.25% acetic acid (A1 series) or 1.25% citric acid (A2 series), with or without the addition of 30% AVG, 0.25% RGE, or both. RGE significantly enhanced antioxidant capacity, especially in non-cross-linked CBEFs (max. 61.2-fold). Citric acid cross-linking improved film thickness and elongation, while reducing WVTR, and slightly decreased antioxidant capacity. FTIR and FE-SEM suggested that RGE primarily interacted via hydrogen bonding and ionic interactions, reinforcing the film matrix. All formulations exhibited antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Xanthomonas campestris. Thermal analysis revealed that A2C3 exhibited the highest Tmax (340 °C) and a pronounced high-temperature endothermic peak (~536.8 °C), indicating superior thermal stability. When applied to cherry tomatoes, A2C3 reduced weight loss (5.27%) and preserved vitamin C (11.2 mg/100 g) over 18 days without affecting sensory acceptance. These findings highlight A2C3 as a promising natural film and coating for the preservation of fresh produce.